A maternal high-fat diet during pregnancy and lactation induced depression-like behavior in offspring and myelin-related changes in the rat prefrontal cortex - Frankowska, Małgorzata; Surówka, Paulina; Gawlińska, Kinga; Borczyk, Małgorzata; Korostyński, Michał; Filip, Małgorzata; Smaga, Irena (Frontiers in Molecular Neuroscience, 2024)
In accordance with the developmental origins of health and disease, early-life environmental exposures, such as maternal diet, can enhance the probability and gravity of health concerns in their offspring in the future. Over the past few years, compelling evidence has emerged suggesting that prenatal exposure to a maternal high-fat diet (HFD) could trigger neuropsychiatric disorders in the offspring, such as depression. The majority of brain development takes place before birth and during lactation. Nevertheless, our understanding of the impact of HFD on myelination in the offspring’s brain during both gestation and lactation remains limited. In the present study, we investigated the effects of maternal HFD (60% energy from fat) on depressive-like and myelin-related changes in adolescent and adult rat offspring. Maternal HFD increased immobility time during the forced swimming test in both adolescent and adult offspring. Correspondingly, the depressive-like phenotype in offspring correlated with dysregulation of several genes and proteins in the prefrontal cortex, especially of myelin-oligodendrocyte glycoprotein (MOG), myelin and lymphocyte protein (MAL), 2′,3′-cyclic-nucleotide 3′-phosphodiesterase (CNPase), kallikrein 6, and transferrin in male offspring, as well as of MOG and kallikrein 6 in female offspring, which persist even into adulthood. Maternal HFD also induced long-lasting adaptations manifested by the reduction of immature and mature oligodendrocytes in the prefrontal cortex in adult offspring. In summary, maternal HFD-induced changes in myelin-related genes are correlated with depressive-like behavior in adolescent offspring, which persists even to adulthood.